Sugarcane outgrowers in Ethiopia: 'Forced' to remain poor? - Mengistu Assefa Wendimu; Arne Henningsen; Peter Gibbon (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2015)
Contract farming is often seen as a panacea to many of the challenges faced by agricultural production in developing countries. Given the large heterogeneity of contract farming arrangements, it is debatable whether all kinds of contract farming arrangements offer benefits to participating smallholders. We apply matching methods to analyze the effects of a public sugarcane outgrower scheme in Ethiopia. Participation in the outgrower scheme significantly reduces the income and asset stocks of outgrowers who contributed irrigated land to the outgrower scheme, while the effect was insignificant for outgrowers who contributed rain-fed land. We provide several explanations and discuss policy implications.
Keywords: Q12; Q13; O13; I31; 330; Productivity; Outgrower scheme; contract farming; sugarcane; propensity score; genetic matching; Ethiopia